2011
DOI: 10.1080/01411921003734645
|View full text |Cite
|
Sign up to set email alerts
|

The impact of support staff on pupils’ ‘positive approaches to learning’ and their academic progress

Abstract: In recent years there has been an unprecedented increase in support staff in schools in England and Wales. There were widespread expectations that this will be of benefit to teachers and pupils but there has been little systematic research to address the impact of support staff. This study used a naturalistic longitudinal design to investigate the relationship between the amount of support (measured by teacher estimates and systematic observation) and pupils’ ‘Positive Approaches to Learning’ (PAL) and academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 21 publications
2
69
0
Order By: Relevance
“…Second, there is evidence that children with SEN spend less time interacting with teachers and far more time with teaching assistants (TAs), who are on average less well qualified than teachers. Indeed, research has indicated that pupils supported by TAs make less progress on average than their similarly able peers (Blatchford et al 2011;Webster and Blatchford 2013). This issue certainly applies to children with statements of SEN who are allocated TA time and may also apply to those children with significant needs who do not have statements but who tend to be supported by TAs.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…Second, there is evidence that children with SEN spend less time interacting with teachers and far more time with teaching assistants (TAs), who are on average less well qualified than teachers. Indeed, research has indicated that pupils supported by TAs make less progress on average than their similarly able peers (Blatchford et al 2011;Webster and Blatchford 2013). This issue certainly applies to children with statements of SEN who are allocated TA time and may also apply to those children with significant needs who do not have statements but who tend to be supported by TAs.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…health and well-being). Most research, however, finds that teaching assistants have a limited effect on educational attainment (Blatchford et al, 2011). This may be because teaching assistants are used inefficiently, rather than because they have little effect per se.…”
Section: Long-run Trends In Per-pupil Expenditurementioning
confidence: 89%
“…The evidence that does exist suggests they have had relatively weak eects on pupil attainment (Blatchford et al (2011);Farrell et al (2010) However, it is important to acknowledge that increases and changes in school resources can be still be valuable even if they do not increase attainment (Cellini et al (2010)). Non-teaching sta could have helped schools achieve wider social objectives, such as improved behaviour, attendance or health.…”
Section: Summary and Discussion Of Resultsmentioning
confidence: 99%